Apa yang seharuisnya anda ketahui tentang merawat pasien stroke / Robert Buckman, Jenny Sutcliffe ; penerjemah, Theodorus Dharma Wibisono ; penyunting, Hingawati Setio, Nur - BUCKMAN, ROBERT; Sutcliffe, Jenny; Theodorus Dharma Wibisono; Hingawati Setio; Nur'aini W. (Citra Aji Parama, 2010)
80 hlm. : ilus. ; 25 cm.